Curbing Health Misinformation With Scientific Journals: A Study Of Nigeria’s Punch And Tribune Online Newspapers - MATYEK, JIMME; Maimoko, Dongvel Dorothy; Ochai, Thomas (Academic Journal of Da'wa and Communication, 2023)
This descriptive research explores the patterns of health news in Punch and Tribune online newspapers from 2018 to 2022, emphasizing the reliance on foreign research by both publications in a bid to curb health misinformation online. With a population of 765 and a sample size of 533, the study reveals Punch's consistent rise in yearly research journal-sourced health news, contrasting with Tribune's fluctuating trend. The Punch heavily favors foreign research (98.1%), while Tribune maintains a more balanced approach with 51.4% from Nigerian sources. The findings underscore disparities in editorial strategies, raising concerns about the visibility of local health research. The study recommends increased collaboration with local researchers and enhanced accessibility of local research, for a more comprehensive and contextually relevant portrayal of health topics to curb health misinformation.